(untitled) (Международный научный журнал «Инженер», 2026)
Flotation enrichment is one of the key stages in the processing technology of non-ferrous and precious metal ores. The efficiency of this process is determined by the physicochemical interactions occurring in the liquid phase and on the surface of the minerals. In the aqueous medium, where the separation of mineral particles takes place, a gaseous phase—air bubbles—exists alongside the solid phase, playing a crucial role in the flotation process. In this context, to identify the flotation capacity of the developed flotation reagentsfoaming agents, it is necessary to study their physicochemical properties, which make it possible to determine their flotation performance. Accordingly, the aim of this work is to investigate the physicochemical properties and flotation capacity of the experimental batches of the composite chemical flotation reagents-foaming agents КХФ-ВС-Б.